2018
DOI: 10.3324/haematol.2018.188987
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, outcomes, and risk factors of pleural effusion in patients receiving dasatinib therapy for Philadelphia chromosome-positive leukemia

Abstract: Dasatinib, a second-generation BCR-ABL1 tyrosine kinase inhibitor, is approved for the treatment of chronic myeloid leukemia and Philadelphia chromosome-positive acute lymphoblastic leukemia, both as first-line therapy and after imatinib intolerance or resistance. While generally well tolerated, dasatinib has been associated with a higher risk for pleural effusions. Frequency, risk factors, and outcomes associated with pleural effusion were assessed in two phase 3 trials (DASISION and 034/Dose-optimization) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 32 publications
1
63
0
3
Order By: Relevance
“…A similar rate (14%) was observed in the phase 3 dasatinib dose optimization study (CA180-034), in which most cases were managed with temporary dose interruption or reduction; only three (1.4%) patients required dasatinib discontinuation due to pleural effusion [25]. The lower incidence of pleural effusion in DASCERN may be due to the relatively young age of the patients, as younger patients have been reported to be at a reduced risk of developing pleural effusion after initiating dasatinib therapy [26]. However, a longer follow-up is required as pleural effusions may occur later in the course of therapy with dasatinib.…”
Section: Discussionmentioning
confidence: 99%
“…A similar rate (14%) was observed in the phase 3 dasatinib dose optimization study (CA180-034), in which most cases were managed with temporary dose interruption or reduction; only three (1.4%) patients required dasatinib discontinuation due to pleural effusion [25]. The lower incidence of pleural effusion in DASCERN may be due to the relatively young age of the patients, as younger patients have been reported to be at a reduced risk of developing pleural effusion after initiating dasatinib therapy [26]. However, a longer follow-up is required as pleural effusions may occur later in the course of therapy with dasatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Pleural effusion is primarily associated with dasatinib, with a 5-year cumulative incidence of 37%. Risk factors include older age, twice daily dosing, previous or concomitant cardiac disease or autoimmune disorders, hypertension, hypercholesterolemia, and advanced phase CML [85]. Diarrhea or constipation may occur with any TKI.…”
Section: Toxicity Side-effects and Complicationsmentioning
confidence: 99%
“…77 Pleural effusion was also more common with dasatinib (28% in the DASISION study compared with ,1% with imatinib and 33% in a dose optimization study) and age has been identified as a significant risk factor for the development of pleural effusion. 78 The occurrence of pleural effusion is significantly reduced with dasatinib 100 mg once daily compared with 70 mg twice daily. Patients with prior cardiac history, with hypertension, and receiving dasatinib 70 mg twice daily are at increased risk of developing pleural effusions.…”
Section: Dasatinibmentioning
confidence: 99%